How do cultural beliefs and the traditional practice of Ukuthwasa perpetuate misconceptions surrounding psychosocial disabilities in Black South African communities? - Grobbelaar-Du Plessis, IIze (University of Pretoria, 2024)
Mini Dissertation (LLM (Multidisciplinary Human Rights))--University of Pretoria, 2023.